STRUCTURAL RELATIONSHIPS BETWEEN PERCEIVED RISK AND CONSUMERS UNWILLINGNESS TO BUY HOME APPLIANCES ONLINE WITH MODERATION OF ONLINE CONSUMER REVIEWS - Syarafina Ibrahim; Norazah Mohd Suki; Amran Harun (Asian Academy of Management Journal, 2014)
This study aims to examine the effect of perceived risk factors (i.e. perceived performance risk, financial risk, time-loss risk, psychological risk and source risk) on consumers' unwillingness to buy home appliances online. The moderation of online consumer reviews with the relationship between perceived risk and consumers' unwillingness to buy home appliances online is also investigated. Results via the Structural Equation Modelling (SEM) technique revealed that perceived performance risk influences consumers' likelihood of not buying home appliances online, as the consumers are themselves unable to touch, see and hear the product. Online consumer reviews have also been found to moderate this relationship. The present study provides important practical contributions that allow retailers and internet marketers to understand consumers' perceptions and behaviours regarding consumer risk perception and to determine which type of risk is most important to address in order to increase the consumers' likelihood of buying home appliances online. This paper also presents a direction for future research.